Tight Junction Pore and Leak Pathways: A Dynamic Duo - Shen, Le (Annu Rev Physiol, 2011)
Tissue barriers that restrict passage of liquids, ions, and larger solutes are essential for the development of multicellular organisms. In simple organisms this allows distinct cell types to interface with the external environment. In more complex species, the diversity of cell types capable of forming barriers increases dramatically. Although the plasma membranes of these barrier-forming cells prevent flux of most hydrophilic solutes, the paracellular, or shunt, pathway between cells must also be sealed. This function is accomplished in vertebrates by the zonula occludens, or tight junction. The tight junction barrier is not absolute but is selectively permeable and is able to discriminate between solutes on the basis of size and charge. Many tight junction components have been identified over the past 20 years, and recent progress has provided new insights into the proteins and interactions that regulate structure and function. This review presents these data in a historical context and proposes an integrated model in which dynamic regulation of tight junction protein interactions determines barrier function.